2019
DOI: 10.3390/su11246977
|View full text |Cite
|
Sign up to set email alerts
|

Failing Services on Urban Waste Management in Developing Countries: A Review on Symptoms, Diagnoses, and Interventions

Abstract: The potential and scale of cities enable economic growth and the improvement of citizens’ access to jobs, education, healthcare, culture, public utilities and services. Solid waste management (SWM) is one of the key services provided by cities. Its operations are complex, very visible to the general public, and impacted by strong financial, societal, and political constraints. Performances in developing countries, however, are not positive. United Nations research shows urban collection services covering no mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 64 publications
(152 reference statements)
2
21
0
Order By: Relevance
“…2 Department of Lifespan Psychology, Faculty of Psychology, Open Universiteit, Heerlen, The Netherlands. 3…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Department of Lifespan Psychology, Faculty of Psychology, Open Universiteit, Heerlen, The Netherlands. 3…”
Section: Supplementary Informationmentioning
confidence: 99%
“…For instance, using lighter plastic composites instead of metal in aircrafts results in significant fuel cost savings as well as easier assembly of airplane parts [ 2 ]. However, some of the properties of plastics, such as longevity and resistance to degradation, create a major waste management problem [ 1 ], especially in developing countries [ 3 ]. A global analysis [ 4 ] showed that approximately 6300 metric tons of plastic waste have been generated as of 2015, of which only 9% have been recycled.…”
Section: Introductionmentioning
confidence: 99%
“…Waste collection is an important part of the environmental policies and represents one of the challenges for public authorities worldwide because as urbanization is increasing, especially in developing countries and growth of population. Ineffective waste management and weak policies may lead to the degradation of valuable land resources, a rise in the land price and the creation of long-term environmental and human health problems [2].…”
Section: Problem Statementmentioning
confidence: 99%
“…Thus, it is vital to choose a refuse disposal site that will have a minimal hazardous effect on human health and the environment. Solid waste management (SWM) has five main pillars: Reduction, recycling, recovery, reuse, and disposal [9][10][11][12][13][14][15][16][17]. Different approaches have been developed to manage MSW, but landfilling has remained the most common approach to manage MSW, mainly in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Due to changes in consumption patterns of commercial and households, the amount of solid waste generated per year has increased globally [9]. Improper management of this waste has led to many environmental problems like contamination of surface and groundwater bodies [18], air pollution [6], lack of land [19], and potential financial obligations [13,18,19].…”
Section: Introductionmentioning
confidence: 99%